2022
DOI: 10.1177/1532673x221112396
|View full text |Cite
|
Sign up to set email alerts
|

Proper Protective (Voting) Equipment: How Covid-19 Safety Measures Shaped In-Person Voting Experiences During the 2020 Election

Abstract: Leading up to the 2020 election, many Americans were worried about casting a ballot in-person due to the Covid-19 pandemic and supported measures to protect voters at the voting booths. Addressing these concerns, election administrators enacted multiple Covid safety measures (e.g., routinely cleaning voting booths, wearing face masks, and providing single use ballot pens). Given voters’ health concerns related to the pandemic and support for safety measures at the ballot box, the presence of Covid safety proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…At the same time, there also appeared to be widespread support for polling place safety measures like social distancing, mask wearing, and sanitization (Douglas and Zilis 2021). Coll (2022a) found that among those who voted in person in 2020, polling place safety measures increased perceptions of safety, although it is not clear if those who did not vote in person were aware these measures were in place or would have been made to feel safer by them. Additionally, Coll (2022b) finds that polling place safety measures increased the amount of time people took to vote, suggesting an important potential downside to these measures if the possibility of longer waits decreased turnout.…”
Section: Theoretical Motivation and Prior Literaturementioning
confidence: 99%
“…At the same time, there also appeared to be widespread support for polling place safety measures like social distancing, mask wearing, and sanitization (Douglas and Zilis 2021). Coll (2022a) found that among those who voted in person in 2020, polling place safety measures increased perceptions of safety, although it is not clear if those who did not vote in person were aware these measures were in place or would have been made to feel safer by them. Additionally, Coll (2022b) finds that polling place safety measures increased the amount of time people took to vote, suggesting an important potential downside to these measures if the possibility of longer waits decreased turnout.…”
Section: Theoretical Motivation and Prior Literaturementioning
confidence: 99%